Suppression of Base Excitation of Rotors on Magnetic Bearings - Steven Marx; C. Nataraj (International Journal of Rotating Machinery)
This paper deals with rotor systems that suffer harmonic base excitation when supported on magnetic bearings. Magnetic bearings using conventional control techniques perform poorly in such situations mainly due to their highly nonlinear characteristics. The compensation method presented here is a novel optimal control procedure with a combination of conventional, proportional, and differential feedback control. A four-degree-of-freedom model is used for the rotor system, and the bearings are modeled by nonlinear expressions. Each disturbance frequency is expected to produce a multiharmonic system response, a characteristic of nonlinear systems. We apply optimal control choosing to minimize a performance index, which leads to the optimization of the trigonometric coefficients in the correction current function. Results show that the control technique suppresses rotor vibration to amplitudes that were significantly smaller than the disturbance amplitudes for the entire range of disturbance frequencies applied. The control technique explored in this paper is a promising step towards the successful application of magnetic bearings to systems mounted on moving platforms.